Brazil - Minas Gerais - World Bank Partnership : Building on a Strong Foundation and Leading to Next Steps - World Bank (2012)
This document, Minas Gerais World Bank partnership: building on a strong foundation and leading to next steps, points the direction for next steps and emphasizes the elements and principles of a possible follow-up operation to the Development Policy Loan (DPL) that completed disbursement in April 2007, recognizing that it was premature to discuss the specifics of such an operation during this exercise. These elements and principles would provide the incentives and motivations for the choice of focus sectors under a possible Bank operation with Minas Gerais. Lead actively by the Governor and Deputy Governor, the Minas authorities have clearly identified enhancing the living conditions of citizens in the state as the overall priority. Nevertheless, the Minas Gerais targets are ambitious and by international standards there is ample room for additional progress. The report points out that fiscal policies and public sector reforms in Minas Gerais could be expected to yield continued stronger than national average economic growth and progress in creating jobs. The focus of this Partnership document is mainly on the Plano Mineiro de Desenvolvimento Integrado (PMDI) 2007-2023 long-term development strategy with an emphasis on broadening reforms. In short, the sectoral assessments are at the heart of the Partnership dialogue and could be used as the foundation for future development of the relationship, especially in areas of technical assistance or future Bank operations with Minas Gerais.